2015
DOI: 10.1161/circresaha.116.303550
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Effects on Hematopoiesis and Atherosclerosis

Abstract: Diet, exercise, stress and sleep are receiving attention as environmental modifiers of chronic inflammatory diseases, including atherosclerosis, the culprit condition of myocardial infarction and stroke. Accumulating data indicate that psychosocial stress and a high-fat, high-cholesterol diet aggravate cardiovascular disease, whereas regular physical activity and healthy sleeping habits help prevent it. Here we raise the possibility that inflammation-associated leukocyte production plays a causal role in lifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 131 publications
3
65
0
1
Order By: Relevance
“…In the present study we observed an increased peripheral monocytosis in apoE −/− mice and this finding is in agreement with other studies [2932]. Previous studies suggest that hypercholesterolemia during aging may be associated with a homeostasis disruption in bone marrow [28, 33–38], leading to an increased entry of monocytes into atherosclerotic plaque [28, 39, 40]. In addition, previous reports revealed that hypercholesterolemia increased the expression of growth factors [41] and that, in this regard, apoE acts to regulate the proliferation of hematopoietic stem/progenitor cells leading to a subsequent expansion of myeloid lineage [28].…”
Section: Discussionsupporting
confidence: 94%
“…In the present study we observed an increased peripheral monocytosis in apoE −/− mice and this finding is in agreement with other studies [2932]. Previous studies suggest that hypercholesterolemia during aging may be associated with a homeostasis disruption in bone marrow [28, 33–38], leading to an increased entry of monocytes into atherosclerotic plaque [28, 39, 40]. In addition, previous reports revealed that hypercholesterolemia increased the expression of growth factors [41] and that, in this regard, apoE acts to regulate the proliferation of hematopoietic stem/progenitor cells leading to a subsequent expansion of myeloid lineage [28].…”
Section: Discussionsupporting
confidence: 94%
“…These agents generally function to reduce inflammation by blocking the expression of inflammatory progenitors (NF-κB: Zhu et al., 2015; COX-2, iNOS: Li et al., 2015), but have also been shown to increase the amount of serotonin and norepinephrine available in the brain (Xu et al., 2010, Ahmed et al., 2014, Ji et al., 2014, Zhu et al., 2015). It should also be noted that diet and exercise can significantly influence the immune system and therefore lifestyle changes may also be useful therapy for inflammation-related psychiatric disorders and cardiovascular disease (reviewed in Nahrendorf and Swirski, 2015). Based on these findings, natural therapies with anti-inflammatory efficacy may represent a useful alternative therapeutic or adjuvant for depressed patients who present with elevated inflammation and may likely reduce CVD risk.…”
Section: Therapeutic Relevancementioning
confidence: 99%
“…Our findings suggest that higher perceived stress was significantly and independently associated with risk of aneurysmal rupture. As possible biological mechanisms underlying the association, it may be that stress (i) causes a surge in blood pressure that contributes to vascular events (Aggarwal et al., ); (ii) activates the hypothalamic–pituitary–adrenal axis, leading to changes in glucocorticoid secretion and increases in circulating catecholamines that collectively and progressively result in vascular endothelial dysfunction (Everson‐Rose et al., ; Poitras & Pyke, ); and (iii) affects the inflammatory pathway in a way that may lead to vascular wall injury (Chalouhi et al., ; Nahrendorf & Swirski, ). Although we did not examine specific mechanistic pathways, these possibilities are plausible because the mechanisms have been proposed to explain the relationship of psychological stress with many other vascular diseases such as stroke that have common features in terms of vascular damage.…”
Section: Discussionmentioning
confidence: 99%